PELATIHAN LUKIS KACA SEBAGAI PEMBERDAYAAN POTENSI KREASI SENI KRIYA DI DESA BANARAN KECAMATAN GEMAWANG KABUPATEN TEMANGGUNG PROPINSI JAWA TENGAH - Rahayu Adi Prabowo (Abdi Seni, 2020)
Thematic community service titled “Glass Painting Training as an Empowerment for the Potential of Creative Arts Creation in Banaran Village Gemawang District Temanggung Regency Central Java Province” This focus is on increasing the potential of craft arts in Banaran Village Gemawang District Temanggung District Central Java Province, namely with a series of glass painting making training as an alternative to the development of craft art creations in Banaran Village. This is important to do because so far the technique of glass painting is more widely known in the arts academics environment without much involving the role of the community in its development. This dedication activity besides introducing one of the painting techniques to the glass media, is also broadly aimed as a foothold in the framework of empowering the creative economy in rural communities. After attending this training, it is expected that emerging creative economic development talents that can uplift the economy of rural communities starting from the movement of the individuals involved will then be predicted to emerge MSMEs (Micro and Small and Medium Enterprises) based on the potential of craft art. The method used in this activity is intensive training which is held for several weeks. The training itself will be divided into 5 stages of work namely; general introduction to theory, introduction to media and glass painting techniques, design practice, application of color tone applications to glass media, and finishing and evaluation.Keywords: craft art, glass painting, creative economy.